2018
DOI: 10.1186/s12890-018-0724-3
|View full text |Cite
|
Sign up to set email alerts
|

Adherence to inhaled therapy and its impact on chronic obstructive pulmonary disease (COPD)

Abstract: BackgroundCOPD is a treatable disease with increasing prevalence worldwide. Treatment aims to stop disease progression, to improve quality of life, and to reduce exacerbations. We aimed to evaluate the association of the stage of COPD on adherence to inhaled therapy and the relationship between adherence and COPD exacerbations.MethodsA retrospective analysis of patients hospitalized for acute exacerbation of COPD in a tertiary care hospital in Upper Austria and discharged with a guideline conform inhaled thera… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
40
2
10

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 69 publications
(64 citation statements)
references
References 37 publications
(40 reference statements)
3
40
2
10
Order By: Relevance
“…However, in previous studies, adherence to inhaler therapy was best in patients who were 65 years or older, male, and had more severe COPD based on GOLD criteria. 6,28,33 The discrepancy between the findings of this and previous studies may be explained by the fact that most participants in this study were elderly men with mild-to-moderate COPD (GOLDⅠ-Ⅱ). Previous studies have reported that poor adherence appears in the initial year of inhalation therapy and that inhalation education improves adherence.…”
contrasting
confidence: 85%
See 1 more Smart Citation
“…However, in previous studies, adherence to inhaler therapy was best in patients who were 65 years or older, male, and had more severe COPD based on GOLD criteria. 6,28,33 The discrepancy between the findings of this and previous studies may be explained by the fact that most participants in this study were elderly men with mild-to-moderate COPD (GOLDⅠ-Ⅱ). Previous studies have reported that poor adherence appears in the initial year of inhalation therapy and that inhalation education improves adherence.…”
contrasting
confidence: 85%
“…6,19 It has been reported that mood disorders may affect the recognition of personal health goals and cause poor adherence. 18,27,28 The study showed a link between the HADS and ASK-20 scores, suggesting that mood disorders may increase the ASK-20 scores. In patients with high ASK-20 scores, it may be necessary to consider the possibility that mood disorders may underlie poor adherence.…”
mentioning
confidence: 92%
“… 28 Nevertheless, adherence to treatments among patients with COPD is especially poor, with rates of non-adherence ranging between 50% and 80%. 29 , 30 Non-adherence to treatment is associated with high mortality and morbidity, number of hospitalizations, and reduced quality of life. 31 Patients with good adherence to inhalers showed 1.9 times higher likelihood of achieving low clinical impact and stability than those with poor adherence rates.…”
Section: Discussionmentioning
confidence: 99%
“…12 Adherence in patients with COPD is particularly poor, with non-adherence rates ranging from 50% to 80%. [13][14][15] Poor adherence is due to many reasons, such as socioeconomic factors, therapy-related factors and patientrelated factors. 16 Specifically, in COPD, there are factors directly related to inhaled therapy such as the complexity of treatment, problems with the use of the device and patients' preferences.…”
Section: Introductionmentioning
confidence: 99%